Strategi Pengembangan Mutu Pendidikan dalam Menghadapi Tantangan Era Digital - Siti Nurmaya; Triwid Syafarotun Najah; Dakir Dakir (INDO PUBLISHING, 2026)
The development of digital technology has brought significant changes to various aspects of life, including education. The digital era presents both opportunities and challenges that require educational institutions to continuously adapt to improve educational quality. This article aims to examine strategies for developing educational quality in response to the challenges of the digital era through an analysis of relevant literature. The method used is a literature review, compiling and analyzing various scientific sources, including journals, books, and educational policy documents related to digital transformation and improving educational quality. The study's results indicate that developing educational quality in the digital era requires a comprehensive strategy, encompassing strengthening teachers' digital competencies, developing a curriculum that adapts to technological developments, optimizing the use of information technology in the learning process, strengthening innovative educational leadership, and developing a digital-based quality assurance system. Furthermore, collaboration between schools, the government, the community, and the technology sector is a crucial factor in supporting the success of educational transformation. Challenges include disparities in access to technology, limited educator digital competency, and the need for adequate infrastructure. Therefore, developing educational quality in the digital era must be carried out sustainably through adaptive policies and strengthening the capacity of all educational stakeholders. This study provides a conceptual contribution to understanding strategies that can be implemented to achieve quality, relevant education that meets the demands of the times.